Recurrent pneumococcal meningitis in a splenectomised HIV-infected patient - Quesne Gilles; Abachin Eric; Poyart Claire; Veuillez Veronique; Morand Philippe C; Dupont Bertrand; Berche Patrick; Viard Jean-Paul (BMC, 2003)
Abstract Background Streptococcus pneumoniae is a major cause of human disease, especially in pre-school children and elderly people, as well as in special risk groups such as asplenic, antibody deficient patients, or presenting disruption of natural barriers. The occurrence of pneumococcal disease has increased with the onset of the HIV epidemic and the emergence of drug-resistance. Case presentation We report the case of an HIV-1-infected patient who experienced three episodes of recurrent pneumococcal meningitis over a 4-year period, despite chemoprophylaxis and capsular vaccination. Conclusions Efficacy of anti-pneumococcal chemoprophylaxis and vaccination in HIV-infected patients are discussed in the light of this particular case.